Prevalence, types, risk factors and clinical correlates of anaemia in older people in a rural Ugandan population. - Joseph O Mugisha; Kathy Baisley; Gershim Asiki; Janet Seeley; Hannah Kuper (PLoS ONE)
Background Studies conducted in high income countries have shown that anaemia is a common medical condition among older people, but such data are scarce in Africa. The objectives of this study were to estimate the prevalence, types, risk factors and clinical correlates of anaemia in older people. Methods Participants were aged (≥ 50) years recruited from a general population cohort from January 2012 to January 2013. Blood samples were collected for assessing hemoglobin, serum ferritin, serum vitamin B12, serum folate, C-reactive protein, malaria infection and stool samples for assessment of hookworm infection. HIV status was assessed using an algorithm for HIV rapid testing. Questionnaires were used to collect data on sociodemographic characteristics and other risk factors for anaemia. Results In total, 1449 people participated (response rate 72.3%). The overall prevalence of anaemia was 20.3 % (95% CI 18.2-22.3%), and this was higher for males (24.1%, 95% CI=20.7-27.7%) than females (17.5%, 95% CI=15.0-20.1%). In males, the prevalence of anaemia increased rapidly with age almost doubling between 50 and 65 years (p-trend<0.001). Unexplained anaemia was responsible for more than half of all cases (59.7%). Anaemia was independently associated with infections including malaria (OR 3.49, 95% CI 1.78-6.82), HIV (OR 2.17, 1.32-3.57) heavy hookworm infection (OR 3.45, 1.73-6.91), low fruit consumption (OR 1.55, 1.05-2.29) and being unmarried (OR 1.37 , 95% CI 1.01-1.89). However, the odds of anaemia were lower among older people with elevated blood pressure (OR 0.47, 95% CI 0.29-0.77). Conclusion Anaemia control programmes in Uganda should target older people and should include interventions to treat and control hookworms and educational programs on diets that enhance iron absorption. Clinicians should consider screening older people with HIV or malaria for anaemia. Further studies should be done on unexplained anaemia and serum ferritin levels that predict iron deficiency anaemia in older people.